Effects of two methods of tooth resection on tooth integrity and piglet behaviour immediately before and after treatment - Anna R.L. Sinclair; Céline Tallet; Paula J. Brunton; Richard B. D’Eath; Dale A. Sandercock; Armelle Prunier (Applied Animal Behaviour Science, 2026)

Predictors of Food Web Resistance to Environmental Change - Javier Jarillo; Jonathan F. Jupke; Tom Sinclair; Lorraine Maltby; Ralf B. Schäfer; Frederik De Laender (Ecology Letters, 2026)
Impacts of environmental change on ecosystems are seemingly highly context‐dependent and contingent on details. Here, we provide mathematical and numerical evidence that there is some generality to the resistance of food webs to species loss. To this end, we mathematically analyse simple food web models, run simulations with randomly wired food webs, develop a spatially explicit meta‐community model for realistic macroinvertebrate communities inhabiting European streams, and analyse field data. These approaches jointly support three general rules for food web resistance: (1) all else equal, predators are more vulnerable than prey, and predator diversity declines before prey diversity; (2) food webs with higher prey diversity tend to be less resistant to environmental change; and (3) food web resistance decreases with the mean taxon tolerance and reaches a maximum at an optimal ratio of predator to prey tolerance. Our findings elucidate characteristics that make food webs vulnerable, fostering more effective conservation practices.

The influence of cold temperature exposure on markers of bone health in humans: A scoping review - R. Allan; H.T. Hurst; B. Akin; N. Liles; J. Dickson; J. Knill-Jones; J. Sinclair; S. Dillon; S.J. Hesketh; C. Mawhinney (Journal of Thermal Biology, 2026)

Novel Method for Collecting Skin Microbiome Samples From Free‐Ranging Bottlenose Dolphin - Joseph J. Hansen; Jennifer C. G. Bloodgood; Brandi Kiel Reese; Thomas B. Waltzek; Kevin Barry; Thibaut Bouveroux; Carrie Sinclair; Kuttichantran Subramaniam; Keith D. Mullin; Ruth H. Carmichael (Marine Mammal Science, 2026)
Cetacean skin microbiome samples are traditionally collected by swabbing the skin of captured animals or using skin tissue from remote biopsies. The effects of different sampling methods are not well understood, and factors such as swab type and storage methods may affect the microbiome. The objective of this study was to determine if samples collected by swabbing biopsied skin from bottlenose dolphins yield sufficient microbial DNA for gene sequencing, while testing if commonly used sampling and storage methods affect the skin microbiome. Skin swab samples were collected during remote biopsy surveys with either a nylon flocked swab and flash frozen with liquid nitrogen or with a cotton swab and stored in RNAlater. Sequencing of the V3–V4 region of the 16S rRNA gene revealed swabs from dolphin skin biopsies yielded sufficient DNA to characterize the microbiome. We found no significant difference between the two sampling and storage methods tested, suggesting that studies using different techniques may be comparable. This work also demonstrates a novel technique to collect samples for interpretation of the skin microbiome of free‐ranging animals. Benefits of this method are that it can be done without capture and preserves valuable and typically scarce biopsy skin samples for other analyses.

Does jurisdictional siloing increase or undermine the efficiency and efficacy of next-generation IA in federalist states? A Canadian example - Anna Johnston; A. John Sinclair; Robert B. Gibson (Environmental Impact Assessment Review, 2025)

Ecological but Not Biological Traits of European Riverine Invertebrates Respond Consistently to Anthropogenic Impacts - James S. Sinclair; Rachel Stubbington; Ralf B. Schäfer; Libuše Barešová; Núria Bonada; Zoltán Csabai; J. Iwan Jones; Aitor Larrañaga; John F. Murphy; Petr Pařil; Marek Polášek; Jes J. Rasmussen; et al. (Global Ecology and Biogeography, 2024)
Aim To determine which riverine invertebrate traits respond consistently to anthropogenic impacts across multiple biogeographic regions. Location Europe. Time Period 1981–2021. Major Taxa Studied Riverine invertebrates. Methods We compiled a database of riverine invertebrate community time series for 673 sites across six European countries spanning six freshwater ecoregions. We compared trait responses to anthropogenic impacts (quantified as changes in ‘ecological quality’) among regions for seven ‘ecological’ traits, which reflect habitat preferences, and nine ‘biological’ traits (e.g., morphology or life history), which represent taxon‐specific attributes that can influence ecosystem processes. Results Four ecological traits (current, microhabitat, salinity and trophic preferences) and one biological trait (dispersal mode) responded consistently across regions. These responses were primarily driven by spatial differences among poorer to better quality sites. Responses to temporal changes in quality were comparable but less pronounced. Main Conclusions Consistent responses to anthropogenic impacts across multiple ecological traits indicate these traits may improve broader scale measurements, comparisons and predictions of community responses. However, we could not use ecological traits to identify the actions of specific stressors because multiple traits always responded as a group. Inconsistent responses across almost all biological traits indicated that these traits may be less predictive of impacts across regions. Predictions of how biological traits, and associated ecosystem processes, respond to anthropogenic impacts may be most effective at regional scales where responses are more consistent.

Dispersal, glacial refugia and temperature shape biogeographical patterns in European freshwater biodiversity - Daniela Cortés‐Guzmán; James Sinclair; Christian Hof; Jan B. Kalusche; Peter Haase (Global Ecology and Biogeography, 2024)
Aim Temperature is regarded as an important driver of broad‐scale biodiversity patterns. However, less is known of the role of dispersal in shaping broad‐scale species and trait distributions, particularly given that species had to disperse out of glacial refugia after the Last Glacial Maximum (LGM). Here, we used a unique dataset describing the distributions of freshwater fauna combined with trait information to evaluate biodiversity relationships to distance to glacial refugia and temperature. Location Twenty‐five biogeographical regions across Europe. Time Period Data from species occurrence were gathered in 1978. Major Taxa Studied A total of 2816 freshwater invertebrate species and 230 freshwater fish species. Methods Using the occurrence of invertebrate and fish species in the biogeographical regions, and publicly available trait information, we analysed patterns in diversity indices (i.e. species richness, trait richness and trait redundancy), trait distribution and species and trait β ‐diversity, and their relationship to distance to known glacial refugia and regional temperature. Results We show that distributions of European invertebrate and fish species and traits are primarily explained by distance to refugia and its covarying effect with temperature (i.e. refugia tend to be warmer). Specifically, species and trait richness were higher in regions proximate to refugia and lower in distant regions. Additionally, communities in colder and distant regions exhibited reduced niche dimensions and slower life histories, suggesting increased vulnerability to environmental change. Main Conclusions Species more distant from their refugia were characterized by higher dispersal capacities. Accordingly, since the LGM, only a subset of species was able to colonize distant regions, while many species have spatial ranges constrained by their dispersal capacity, increasing their potential for extinction under ongoing climate change. Therefore, additional conservation measures considering species' dispersal capacities are required.

The imperative of arachidonic acid in early human development - Michael A. Crawford; Andrew J. Sinclair; Barbara Hall; Enitan Ogundipe; Yiqun Wang; Dimitrios Bitsanis; Ovrang B. Djahanbakhch; Laurence Harbige; Kebreab Ghebremeskel; Ivan Golfetto; Therishnee Moodley; Ahmed Hassam; et al. (Progress in Lipid Research, 2023)

Polanyi adsorption potential theory for estimating PFAS treatment with granular activated carbon - Jonathan B. Burkhardt; Adam Cadwallader; Jonathan G. Pressman; Matthew L. Magnuson; Antony J. Williams; Gabriel Sinclair; Thomas F. Speth (Journal of Water Process Engineering, 2023)

Regional versus latitudinal variation in the life‐history traits and demographic rates of a reef fish, Centropyge bispinosa , in the Coral Sea and Great Barrier Reef Marine Parks, Australia - Jake R. Lowe; Samuel D. Payet; Hugo B. Harrison; Jean‐Paul A. Hobbs; Andrew S. Hoey; Brett M. Taylor; Tane H. Sinclair‐Taylor; Morgan S. Pratchett (Journal of Fish Biology, 2021)
Environmental temperature is an important determinant of physiological processes and life histories in ectotherms. Over latitudinal scales, variation in temperature has been linked to changes in life‐history traits and demographic rates, with growth and mortality rates generally being greatest at low latitudes, and longevity and maximum length being greater at higher latitudes. Using the two‐spined angelfish, Centropyge bispinosa , as our focal species, we compared growth patterns, growth rates, longevity, mortality, asymptotic length and maximum length across 22 reefs that span 13° of latitude within the Great Barrier Reef Marine Park (GBRMP) and the Coral Sea Marine Park (CSMP), Australia. We found no predictable latitudinal variation in mortality rates, growth patterns, growth rates, asymptotic or maximum length of C. bispinosa at regional to biogeographic scales. However, C. bispinosa consistently exhibited reduced longevity at lower, warmer latitudes within the CSMP. The greatest differences in mean maximum length of C. bispinosa were between continental (GBRMP) and oceanic (central CSMP) reefs of similar latitude, with individuals being larger on average on continental versus oceanic reefs. The lack of predictable life‐history and demographic variation in C. bispinosa across a 13° latitudinal gradient within the CSMP, coupled with differences in mean maximum length between continental and oceanic reefs at similar latitudes, suggest that local environmental conditions have a greater influence than environmental temperature on the demographic rates and life‐history traits of C. bispinosa .

Maturation in Atlantic salmon (Salmo salar, Salmonidae): a synthesis of ecological, genetic, and molecular processes - Kenyon B. Mobley; Tutku Aykanat; Yann Czorlich; Andrew House; Johanna Kurko; Antti Miettinen; Jacqueline Moustakas-Verho; Andrés Salgado; Marion Sinclair-Waters; Jukka-Pekka Verta; Craig R. Primmer (Reviews in Fish Biology and Fisheries, 2021)
Over the past decades, Atlantic salmon ( Salmo salar, Salmonidae) has emerged as a model system for sexual maturation research, owing to the high diversity of life history strategies, knowledge of trait genetic architecture, and their high economic value. The aim of this synthesis is to summarize the current state of knowledge concerning maturation in Atlantic salmon, outline knowledge gaps, and provide a roadmap for future work. We summarize the current state of knowledge: 1) maturation in Atlantic salmon takes place over the entire life cycle, starting as early as embryo development, 2) variation in the timing of maturation promotes diversity in life history strategies, 3) ecological and genetic factors influence maturation, 4) maturation processes are sex-specific and may have fitness consequences for each sex, 5) genomic studies have identified large-effect loci that influence maturation, 6) the brain-pituitary–gonadal axis regulates molecular and physiological processes of maturation, 7) maturation is a key component of fisheries, aquaculture, conservation, and management, and 8) climate change, fishing pressure, and other anthropogenic stressors likely have major effects on salmon maturation. In the future, maturation research should focus on a broader diversity of life history stages, including early embryonic development, the marine phase and return migration. We recommend studies combining ecological and genetic approaches will help disentangle the relative contributions of effects in different life history stages to maturation. Functional validation of large-effect loci should reveal how these genes influence maturation. Finally, continued research in maturation will improve our predictions concerning how salmon may adapt to fisheries, climate change, and other future challenges.

Consistent and transient drivers of freshwater zooplankton communities - James S. Sinclair; Shelley E. Arnott; William A. Nelson; Kaitlyn B. Brougham (Journal of Biogeography, 2021)
Aim Inferences of the predominant processes that structure communities are commonly based on single ‘snapshots’ in time, which may miss temporally transient but important mechanisms. In this study, we compared key environmental and spatial drivers of zooplankton composition across multiple years to quantify shifts in their relative importance through time, and to identify any drivers of temporal change. Location Southern Ontario, Canada. Taxon Zooplankton. Methods Zooplankton were collected from 29 lakes in southern Ontario, Canada over four years (2013–2016). Variation partitioning was used to quantify the relative importance of independent and covarying components of local environmental conditions, regional east‐west and north‐south compositional trends, and inter‐lake geographic distance in each year. Measured environmental metrics included aspects of lake morphology and chemistry, and spatial relationships were quantified using lake latitude/longitude coordinates and Moran's Eigenvector Maps (MEMs). Redundancy analyses (RDAs) were also used to compare the influence of individual environmental and spatial variables across years. Results Most local‐scale and regional‐scale community processes were consistently important across all surveyed years, but some were less consistent. Specifically, geomorphology was always an important driver of local environmental and regional spatial community patterns. This occurred because local community composition was strongly affected by whether a lake was shallower versus deeper, and due to spatial clusters of shallow and deep lakes that produced negative spatial autocorrelation in community composition. Conversely, the individual influences of lake chemistry and spatial east‐west compositional trends were important in some years and not in others, potentially due to inter‐annual shifts in the predominant environmental variables and extreme weather events. Main conclusions A single‐year community snapshot can provide insight into consistent or slowly changing community structuring processes, such as those driven by geomorphology, but may not completely capture temporally transient mechanisms. Furthermore, snapshots collected during anomalous seasons or years may misrepresent which mechanisms are predominantly determining community composition. Future efforts to understand local and regional community drivers would therefore benefit from considering which processes are likely temporally ‘consistent’ versus ‘transient’, and studies with more variable components would benefit from considering or controlling for temporal shifts in their importance.

Comparative demography of commercially important species of coral grouper, Plectropomus leopardus and P. laevis , from Australia's great barrier reef and Coral Sea marine parks - Samuel D. Payet; Jake R. Lowe; Bruce D. Mapstone; Morgan S. Pratchett; Tane H. Sinclair‐Taylor; Brett M. Taylor; Peter A. Waldie; Hugo B. Harrison (Journal of Fish Biology, 2020)
Understanding the spatial and environmental variation in demographic processes of fisheries target species, such as coral grouper (Genus: Plectropomus ), is important for establishing effective management and conservation strategies. Herein we compare the demography of Plectropomus leopardus and P. laevis between Australia's Great Barrier Reef Marine Park (GBRMP), which has been subject to sustained and extensive fishing pressure, and the oceanic atolls of Australia's Coral Sea Marine Park (CSMP), where there is very limited fishing for reef fishes. Coral grouper length‐at‐age data from contemporary and historical otolith collections across 9.4 degrees of latitude showed little difference in lifetime growth between GBRMP and CSMP regions. Plectropomus laevis populations in GBRMP reefs had significantly higher rates of total mortality than populations in the CSMP. Mean maximum lengths and mean maximum ages of P. laevis were also smaller in the GBRMP than in the CSMP, even when considering populations sampled within GBRMP no‐take marine reserves (NTMRs). Plectropomus leopardus , individuals were on average smaller on fished reefs than NTMRs in the GBRMP, but all other aspects of demography were broadly similar between regions despite the negligible levels of fishing pressure in the CSMP. Similarities between regions in growth profiles and length‐at‐age comparisons of P. laevis and P. leopardus suggest that the environmental differences between the CSMP and the GBRMP may not have significant impacts on lifetime growth. Our results show that fishing may have influenced the demography of coral grouper on the GBR, particularly for the slower growing and longer lived species, P. laevis .

Cranial morphological scaling and relative prey size limitations for a native predator in an invaded system - Eliza I. Gilbert; Scott L. Durst; Angela P. James; Jason E. Davis; Thomas B. Sinclair; Nathan R. Franssen (Environmental Biology of Fishes, 2018)

Recovery following a marathon: a comparison of cold water immersion, whole body cryotherapy and a placebo control - Laura J. Wilson; Emma Cockburn; Katherine Paice; Scott Sinclair; Tanwir Faki; Frank A. Hills; Marcela B. Gondek; Alyssa Wood; Lygeri Dimitriou (European Journal of Applied Physiology, 2018)

Microbial changes linked to the accelerated degradation of the herbicide atrazine in a range of temperate soils - R. L. Yale; M. Sapp; C. J. Sinclair; J. W. B. Moir (Environmental Science and Pollution Research, 2017)

Can we predict ectotherm responses to climate change using thermal performance curves and body temperatures? - Brent J. Sinclair; Katie E. Marshall; Mary A. Sewell; Danielle L. Levesque; Christopher S. Willett; Stine Slotsbo; Yunwei Dong; Christopher D. G. Harley; David J. Marshall; Brian S. Helmuth; Raymond B. Huey (Ecology Letters, 2016)
Thermal performance curves ( TPC s), which quantify how an ectotherm's body temperature ( T b ) affects its performance or fitness, are often used in an attempt to predict organismal responses to climate change. Here, we examine the key – but often biologically unreasonable – assumptions underlying this approach; for example, that physiology and thermal regimes are invariant over ontogeny, space and time, and also that TPC s are independent of previously experienced T b. We show how a critical consideration of these assumptions can lead to biologically useful hypotheses and experimental designs. For example, rather than assuming that TPC s are fixed during ontogeny, one can measure TPC s for each major life stage and incorporate these into stage‐specific ecological models to reveal the life stage most likely to be vulnerable to climate change. Our overall goal is to explicitly examine the assumptions underlying the integration of TPC s with T b , to develop a framework within which empiricists can place their work within these limitations, and to facilitate the application of thermal physiology to understanding the biological implications of climate change.

A review of contemporary patterns of endemism for shallow water reef fauna in the Red Sea - Joseph D. DiBattista; May B. Roberts; Jessica Bouwmeester; Brian W. Bowen; Darren J. Coker; Diego F. Lozano‐Cortés; J. Howard Choat; Michelle R. Gaither; Jean‐Paul A. Hobbs; Maha T. Khalil; Marc Kochzius; Robert F. Myers; et al. (Journal of Biogeography, 2016)
Aim The Red Sea is characterised by a unique fauna and historical periods of desiccation, hypersalinity and intermittent isolation. The origin and contemporary composition of reef‐associated taxa in this region can illuminate biogeographical principles about vicariance and the establishment (or local extirpation) of existing species. Here we aim to: (1) outline the distribution of shallow water fauna between the Red Sea and adjacent regions, (2) explore mechanisms for maintaining these distributions and (3) propose hypotheses to test these mechanisms. Location Red Sea, Gulf of Aden, Arabian Sea, Arabian Gulf and Indian Ocean. Methods Updated checklists for scleractinian corals, fishes and non‐coral invertebrates were used to determine species richness in the Red Sea and the rest of the Arabian Peninsula and assess levels of endemism. Fine‐scale diversity and abundance of reef fishes within the Red Sea were explored using ecological survey data. Results Within the Red Sea, we recorded 346 zooxanthellate and azooxanthellate scleractinian coral species of which 19 are endemic (5.5%). Currently 635 species of polychaetes, 211 echinoderms and 79 ascidians have been documented, with endemism rates of 12.6%, 8.1% and 16.5% respectively. A preliminary compilation of 231 species of crustaceans and 137 species of molluscs include 10.0% and 6.6% endemism respectively. We documented 1071 shallow fish species, with 12.9% endemic in the entire Red Sea and 14.1% endemic in the Red Sea and Gulf of Aden. Based on ecological survey data of endemic fishes, there were no major changes in species richness or abundance across 1100 km of Saudi Arabian coastline. Main conclusions The Red Sea biota appears resilient to major environmental fluctuations and is characterized by high rates of endemism with variable degrees of incursion into the Gulf of Aden. The nearby Omani and Arabian Gulfs also have variable environments and high levels of endemism, but these are not consistently distinct across taxa. The presence of physical barriers does not appear to explain species distributions, which are more likely determined by ecological plasticity and genetic diversity.

Diversity enhances carbon storage in tropical forests - L. Poorter; M. T. van der Sande; J. Thompson; E. J. M. M. Arets; A. Alarcón; J. Álvarez‐Sánchez; N. Ascarrunz; P. Balvanera; G. Barajas‐Guzmán; A. Boit; F. Bongers; F. A. Carvalho; et al. (Global Ecology and Biogeography, 2015)
Aim Tropical forests store 25% of global carbon and harbour 96% of the world's tree species, but it is not clear whether this high biodiversity matters for carbon storage. Few studies have teased apart the relative importance of forest attributes and environmental drivers for ecosystem functioning, and no such study exists for the tropics. Location Neotropics. Methods We relate aboveground biomass ( AGB ) to forest attributes (diversity and structure) and environmental drivers (annual rainfall and soil fertility) using data from 144,000 trees, 2050 forest plots and 59 forest sites. The sites span the complete latitudinal and climatic gradients in the lowland Neotropics, with rainfall ranging from 750 to 4350 mm year −1 . Relationships were analysed within forest sites at scales of 0.1 and 1 ha and across forest sites along large‐scale environmental gradients. We used a structural equation model to test the hypothesis that species richness, forest structural attributes and environmental drivers have independent, positive effects on AGB . Results Across sites, AGB was most strongly driven by rainfall, followed by average tree stem diameter and rarefied species richness, which all had positive effects on AGB . Our indicator of soil fertility (cation exchange capacity) had a negligible effect on AGB , perhaps because we used a global soil database. Taxonomic forest attributes (i.e. species richness, rarefied richness and Shannon diversity) had the strongest relationships with AGB at small spatial scales, where an additional species can still make a difference in terms of niche complementarity, while structural forest attributes (i.e. tree density and tree size) had strong relationships with AGB at all spatial scales. Main conclusions Biodiversity has an independent, positive effect on AGB and ecosystem functioning, not only in relatively simple temperate systems but also in structurally complex hyperdiverse tropical forests. Biodiversity conservation should therefore be a key component of the UN Reducing Emissions from Deforestation and Degradation strateg y.

A unified gene catalog for the laboratory mouse reference genome - Y. Zhu; J. E. Richardson; P. Hale; R. M. Baldarelli; D. J. Reed; J. M. Recla; R. Sinclair; T. B. K. Reddy; C. J. Bult (Mammalian Genome, 2015)

The repeated bout effect of typical lower body strength training sessions on sub-maximal running performance and hormonal response - Kenji Doma; Moritz Schumann; Wade H. Sinclair; Anthony S. Leicht; Glen B. Deakin; Keijo Häkkinen (European Journal of Applied Physiology, 2015)

Genetic diversity in threatened Posidonia australis seagrass meadows - Suzanna M. Evans; Elizabeth A. Sinclair; Alistair G. B. Poore; Peter D. Steinberg; Gary A. Kendrick; Adriana Vergés (Conservation Genetics, 2014)

Divergent transcriptional responses to low temperature among populations of alpine and lowland species of N ew Z ealand stick insects ( M icrarchus ) - Luke T. Dunning; Alice B. Dennis; Brent J. Sinclair; Richard D. Newcomb; Thomas R. Buckley (Molecular Ecology, 2014)
In widespread and genetically structured populations, temperature variation may lead to among‐population differentiation of thermal biology. The New Zealand stick insect genus Micrarchus contains four species that inhabit different thermal environments, two of which are geographically widespread. RNA ‐Seq and quantitative PCR were used to investigate the transcriptional responses to cold shock among lowland and alpine species to identify cold‐responsive transcripts that differ between the species and to determine whether there is intraspecific geographical variation in gene expression. We also used mitochondrial DNA , nuclear 28S ribosomal DNA and transcriptome‐wide SNP s to determine phylogeographic structure and the potential for differences in genetic backgrounds to contribute to variation in gene expression. RNA ‐Seq identified 2160 unigenes that were differentially expressed as a result of low‐temperature exposure across three populations from two species ( M. hystriculeus and M. nov. sp. 2), with a majority (68% ± 20%) being population specific. This extensive geographical variation is consistent across years and is likely a result of background genetic differences among populations caused by genetic drift and possibly local adaptation. Responses to cold shock shared among alpine M. nov. sp. 2 populations included the enrichment of cuticular structure‐associated transcripts, suggesting that cuticle modification may have accompanied colonization of low‐temperature alpine environments and the development of a more cold‐hardy phenotype.

Conserving large populations of lions – the argument for fences has holes - S. Creel; M. S. Becker; S. M. Durant; J. M'Soka; W. Matandiko; A. J. Dickman; D. Christianson; E. Dröge; T. Mweetwa; N. Pettorelli; E. Rosenblatt; P. Schuette; et al. (Ecology Letters, 2013)
Packer et al . reported that fenced lion populations attain densities closer to carrying capacity than unfenced populations. However, fenced populations are often maintained above carrying capacity, and most are small. Many more lions are conserved per dollar invested in unfenced ecosystems, which avoid the ecological and economic costs of fencing.

Identification of calanoid copepod prey species via molecular detection of carbon fixation genes - Wilford B. Boling; Geoff A. Sinclair; Boris Wawrik (Marine Biology, 2012)

Thermal biology of the alien ground beetle Merizodus soledadinus introduced to the Kerguelen Islands - L. Lalouette; C. M. Williams; M. Cottin; B. J. Sinclair; D. Renault (Polar Biology, 2012)

Invasive species can't cover their tracks: using microsatellites to assist management of starling ( Sturnus vulgaris ) populations in Western Australia - LEE ANN ROLLINS; ANDREW P. WOOLNOUGH; ALAN N. WILTON; RON SINCLAIR; WILLIAM B. SHERWIN (Molecular Ecology, 2009)
Invasive species are known to cause environmental and economic damage, requiring management by control agencies worldwide. These species often become well established in new environments long before their detection, resulting in a lack of knowledge regarding their history and dynamics. When new invasions are discovered, information regarding the source and pathway of the invasion, and the degree of connectivity with other populations can greatly benefit management strategies. Here we use invasive common starling ( Sturnus vulgaris ) populations from Australia to demonstrate that genetic techniques can provide this information to aid management, even when applied to highly vagile species over continental scales. Analysis of data from 11 microsatellites in 662 individuals sampled at 17 localities across their introduced range in Australia revealed four populations. One population consisted of all sampling sites from the expansion front in Western Australia, where control efforts are focused. Despite evidence of genetic exchange over both contemporary and historical timescales, gene flow is low between this population and all three more easterly populations. This suggests that localized control of starlings on the expansion front may be an achievable goal and the long‐standing practice of targeting select proximal eastern source populations may be ineffective on its own. However, even with low levels of gene flow, successful control of starlings on the expansion front will require vigilance, and genetic monitoring of this population can provide essential information to managers. The techniques used here are broadly applicable to invasive populations worldwide.

A 3D modeling method to calculate the surface areas of coral branches - A. M. Jones; N. E. Cantin; R. Berkelmans; B. Sinclair; A. P. Negri (Coral Reefs, 2008)

Ethical and welfare considerations when using cephalopods as experimental animals - N. A. Moltschaniwskyj; K. Hall; Marek R. Lipinski; J. E. A. R. Marian; M. Nishiguchi; M. Sakai; D. J. Shulman; B. Sinclair; D. L. Sinn; M. Staudinger; R. Van Gelderen; R. Villanueva; et al. (Reviews in Fish Biology and Fisheries, 2007)

Reduced inflammatory potential of peritoneal macrophages recruited in mice pretreated with a glycolipid synthesis inhibitor - H. C. Yohe; T. J. Kitzmiller; W. J. Bement; B. E. Dwyer; J. F. Sinclair (Inflammopharmacology, 2006)

Consequences of Transferring Three Sorghum Genes for Secondary Metabolite (Cyanogenic Glucoside) Biosynthesis to Grapevine Hairy Roots - T. K. Franks; K. S. Powell; S. Choimes; E. Marsh; P. Iocco; B. J. Sinclair; C. M. Ford; R. van Heeswijck (Transgenic Research, 2006)

Population status and gender imbalance of the marula tree, Sclerocarya birrea subsp. caffra in northern Namibia - Elizabeth Nghitoolwa; John B. Hall; Fergus L. Sinclair (Agroforestry Systems, 2003)

Essential genes in proximal 3L heterochromatin of Drosophila melanogaster - S. Schulze; D. A. R. Sinclair; E. Silva; K. A. Fitzpatrick; M. Singh; V. K. Lloyd; K. A. Morin; J. Kim; D. G. Holm; J. A. Kennison; B. M. Honda (Molecular Genetics and Genomics, 2001)

The effects of traits of Bacillus megaterium onseed and root colonization and their correlation withthe suppression of Rhizoctonia root rot of soybean - X. Y. Zheng; J. B. Sinclair (BioControl, 2000)

Regional Patterns of Streamwater Acidity and Catchment Afforestation in Galloway, SW Scotland - Christoph B. Puhr; Daniel N. M. Donoghue; Alastair B. Stephen; David J. Tervet; Callum Sinclair (Water, Air, & Soil Pollution, 2000)

Regeneration of transgenic vegetable brassicas (Brassica oleracea and B. campestris) via Ri-mediated transformation - M. C. Christey; B. K. Sinclair; R. H. Braun; L. Wyke (Plant Cell Reports, 1997)

Regeneration of transgenic vegetable brassicas (Brassica oleracea andB. campestris) via Ri-mediated transformation - M. C. Christey; B. K. Sinclair; R. H. Braun; L. Wyke (Plant Cell Reports, 1997)

Highly Differentiated Populations of the Narrow Endemic Plant Maguire Primrose ( Primula maguirei ) - Paul G. Wolf; Robert B. Sinclair (Conservation Biology, 1997)
Maguire primrose (Primula maguirei) is a geographically restricted plant species, known only from a 19‐km stretch of Logan Canyon in northern Utah (U.S.A.). We examined variation at 13 isozyme loci from 25 individuals of P. maguirei at each of eight sites. At individual loci we detected no statistically significant deviations from Hardy‐Weinberg proportions within sites (subpopulations). However, some loci were almost fixed for different alleles at the upper reaches of the species’ range relative to populations approximately 10 km away. The total mean gene diversity among loci was 0.22, of which 55% was partitioned within subpopulations, 0.7% among subpopulations within populations (100 m spatial scale), 3% among populations separated by about 1 km, and 41% between an Upper Canyon group of populations and a Lower Canyon group (10‐km scale). We detected no gametic disequilibria among loci within subpopulations (and populations). Two hypotheses are proposed to explain the results: (1) past genetic bottlenecks and (2) genetic divergence as a by‐product of local adaptations to different habitats. Regardless of the causes of allozymic differentiation, our results suggest that plans for artificial establishment or reestablishment of P. maguirei populations should use source populations within 1 km of the establishment site. This study emphasizes the potential use of data on population genetic structure for managing and monitoring rare species.

Incorporation of indigenous knowledge and perspectives in agroforestry development - D. H. Walker; F. L. Sinclair; B. Thapa (Agroforestry Systems, 1995)

Incorporation of indigenous knowledge and perspectives in agroforestry development - B. Thapa; F. L. Sinclair; D. H. Walker (Agroforestry Systems, 1995)

Characterization of an antigenic site on glycoprotein 13 (gC) of equid herpesvirus type-1 - R. Sinclair; B. J. Moult; J. A. Mumford (Archives of Virology, 1993)

New Publications - J. B. Sinclair; Ken Pegg; A. C. Hayward (Australasian Plant Pathology, 1981)

“Biology and Pathology of Macrophimina phaseolina - O. D. Dhingra; J. B. Sinclair (Australasian Plant Pathology, 1978)

“An annoted bibliography of chickpea diseases 191 5-1 976” - Y. L. Nene; A. Mengitsu; J. B. Sinclair; D. J. Royse (Australasian Plant Pathology, 1978)